Paleoecology During the Creation of a Large Boldyrevo Kurgan of the Yamnaya Culture in the Southern Cis-Urals, Russia - Khokhlova, Olga; Sverchkova, Alena; Morgunova, Nina; Golyeva, Aleksandra; Tregub, Tamara (TÁJÖKOLÓGIAI LAPOK, 2022)
This study focuses on a short-term pedochronosequence of Kurgan № 1 at the Boldyrevo IV kurgan cemetery in the Orenburg Region of the Southern Cis-Urals. According to archaeological findings, the kurgan was built over several decades by people of the Yamnaya (Pit-Grave) culture of the Early Bronze Age (around 5500 BP), with the exact time of its building to be confirmed by radiocarbon dating and further archaeological information. A comparative analysis of the four earthen constructions of the kurgan and the paleosols buried under those constructions was conducted. Results suggest that the kurgan building period was accompanied by the following changes in paleosol morphology and physicochemical properties: the humus horizon acquired a tonguing-like lower boundary, decreased organic carbon content and magnetic susceptibility, while the whole profile was characterized by increasing degree of zooturbation; the impregnation by carbonates in the middle part of the profile and the contents of carbonate carbon, gypsum, and exchangeable sodium increased. Similar trends of morphological and physicochemical changes were observed in the materials of the kurgan constructions. Based on these findings it can conclude that the climate went through aridization rise during the period of the kurgan building. The paleobotanical data from palynological and microbiomorphic analyses indicate that there was a tendency for paleoclimate aridization and, possibly a cooling trend during the studied period of the Yamnaya culture, which was probably more arid than the modern climate.
Keywords: burial mound (kurgan); paleosols; short-term pedochronosequence; phytoliths; paleoclimatic reconstruction